The Bees in Your Backyard A Guide to North America's Bees - Wilson, Joseph S. 1980- (Princeton University Press, 2016)
The Bees in Your Backyard provides an engaging introduction to the roughly 4,000 different bee species found in the United States and Canada, dispelling common myths about bees while offering essential tips for telling them apart in the field.The book features more than 900 stunning color photos of the bees living all around us—in our gardens and parks, along nature trails, and in the wild spaces between. It describes their natural history, including where they live, how they gather food, their role as pollinators, and even how to attract them to your own backyard. Ideal for amateur naturalists and experts alike, it gives detailed accounts of every bee family and genus in North America, describing key identification features, distributions, diets, nesting habits, and more.Provides the most comprehensive and accessible guide to all bees in the United States and CanadaFeatures more than 900 full-color photosOffers helpful identification tips and pointers for studying beesIncludes a full chapter on how to attract bees to your backyard
Description based on online resource; title from PDF title page (publisher's Web site, viewed Mar. 30, 2016)
Keywords: Bee culture -- North America; Bees -- North America -- Identification; Bumblebees -- North America; Honeybee -- North America; Nordamerika